1956
DOI: 10.1149/1.2430391
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Fluorescence in the System Zinc Oxide-Boric Oxide

Abstract: TIN-STEEL COUPLE IN AIR-FREE SOLUTION 491anodic effects. The corroding potential thus serves to give a direct indication of the corrosion rate. Unfortunately, it must be cautioned that this relationship cannot be generally extended to corrosion relationships in fruits or fruit juices. ACKNOWLEDGMENTResults presented in this paper were obtained in connection with a project on the corrosion of tin plate sponsored by the Inland Steel Co. The author wishes to thank this organization, and in particular Dr. E. D. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

1963
1963
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 1 publication
6
31
0
Order By: Relevance
“…(1318 K) The transformation points of e 1 and p 1 were reported by Levin et al 9) and the points e 2 , e 3 , e 4 and e 5 were reported by Harrison et al 10) In the region examined in the present study, three ternary eutectic reactions E 1 , E 2 and E 3 exist. Those reactions, temperatures, and eutectic compositions are as follows: In Fig.…”
Section: Liquidus Surfaces Of the Pseudo-ternary Systemsupporting
confidence: 80%
See 2 more Smart Citations
“…(1318 K) The transformation points of e 1 and p 1 were reported by Levin et al 9) and the points e 2 , e 3 , e 4 and e 5 were reported by Harrison et al 10) In the region examined in the present study, three ternary eutectic reactions E 1 , E 2 and E 3 exist. Those reactions, temperatures, and eutectic compositions are as follows: In Fig.…”
Section: Liquidus Surfaces Of the Pseudo-ternary Systemsupporting
confidence: 80%
“…Figure 1 shows compositions of the prepared specimens together with the diagrams of the pseudo-binary BaO-B 2 O 3 and ZnO-B 2 O 3 systems. 9,10) The following vertical pseudo-binary sections of the pseudo-ternary BaOZnO-B 2 O 3 system were selected for analyses of the liquidus surfaces. The isothermal section at 973 K and the liquidus surfaces of the phase diagram of the pseudo-ternary BaO-ZnO-B 2 O 3 system were determined by the thermal analysis, differential thermal analysis (DTA), and X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binary system ZnO-B203 has been studied by several workers (Harrison & Hummel, 1956;Bauer, 1963;Weir & Schroeder, 1964). Fayos, Garcia-Blanco & Rivoir (1966) investigated the system using calcined samples.…”
Section: Introductionmentioning
confidence: 99%
“…Swanson and Tatge [4] reported an X-ray pattern for a cubic form of ZnO.B~O3, while some time later Harrison and Hummel [5] redetermined the entire system using X-ray, quench and differential thermal analysis techniques. They reported the existence of two phases ZnO.B203 and 5ZnO.2B~Oa and also that both were polymorphic.…”
Section: Previous Workmentioning
confidence: 99%